Factores de riesgo asociados a desgarros Vulvoperineales en puérperas atendidas en el Hospital Regional de Loreto, Enero – Abril del 2013 - Pérez Torres, Miguel Ángel (2014)
This research entitled "Risk factors associated with postpartum tears in vulvoperineal treated at the Regional Hospital of Loreto, January-April 2013" ; retrospective correlational quantitative study aimed to identify risk factors associated with vulvoperineal tears, the population consisted of all Postpartum women who had diagnosis of vulvo-perineal tear postpartum amounting to 115. The information was obtained from perinatal clinical histories and 2000 Perinatal Information system recorded in formats adapted to the study and organized in a computerized database with Microsoft Excel 2011 software. The results, 115 vulvoperineal tears in four months, the study population was characterized as cohabiting 71.3 % (82 ) , complete primary education 37.3 % (43 ) 23.4 % and incomplete ( 27), 54.7 % of urban origin (urban ) housewife occupancy 84.3 % (97 ) . The salient maternal risk factors are age 21 to 30 years, mild anemia, the horizontal position and status of gilts, as risk factors for delivery I have instrumental delivery , episiotomy and weight to 4000g RN 3501 We conclude that maternal factors : age ( x2 = 14.03) , anemia ( x2 = 12.75) , maternal position ( x2 = 8.03) and parity ( x2 = 13.69 ); and delivery factors , use of episiotomy ( x2 = 17.84 ) and birth weight ( x2 = 13.91 ) , are associated with it Vulvo tear in puerperal women attended the Loreto Regional Hospital during the months of January to April 2013.